Effect of vitamin D receptor foKI gene polymorphism on chronic renal disease - Kucuksu, Mehmet; Cetinkaya, Ramazan; Ozdemir, Fethi Ahmet; Sarikaya, Metin; Sari, Funda; Gozels, Nevzat (Mattioli 1885, 2019)
Many factors play a role in the progression of Chronic renal disease. Many polymorphisms have been detected in vitamin D receptor gene. FokI polymorphism is one of these. We aimed to present the role played by FokI gene polymorphism in CRD have been examined. Three study groups were formed as group 1 with a total of 60 patients with RRT need with ages ranging between 59,43 +/- 12,58, group 2 with a total of 60 patients with GFR decrease of >4 ml/min/year and ages ranging between 59,73 +/- 13,14 and group 3 with a total of 60 patients with stable GFR level during follow up period with ages ranging between 63,50 +/- 12,21. A total of 77 individuals without CRD and with ages ranging between 41.78 +/- 14,28 were included as the control group of the study during polyclinic controls. The frequency of FokI polymorphism FF, Ff and ff genotypes were determined as 51.7%, 35.0% and 13.3% respectively in group 1, as 50.0%, 41.7% and 8.3% respectively in group 2 and as 45.0%, 48.3% and 6.7% respectively in group 3. Whereas the frequency of FF, Ff and ff genotypes were determined respectively as %51.9, %39.0 and %9.1. Prevalence of CRD in all genotypes was determined to be statistically significant for all groups (p>0.05). No relationship was determined between Fold polymorphism and risk factors. In conclusion, it was observed that Fold polymorphism is not related with CRD and risk factors.
Keywords: Chronic renal disease; fokI polymorphism; renal replacement therapy; rapid progression